1976
DOI: 10.1288/00005537-197604000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of nasal secretions: Further diagnostic help

Abstract: Nasal cytograms, as an aid to diagnosis of pathological conditions of the nose and paranasal sinuses, have not been adopted by the majority of otolaryngologists. This situation exists because of technical problems with the preparation of a slide and the difficulty in finding someone competent and interested in its interpretation. The work of the Bryans has provided an analysis of the cytology of nasal secretions. Adopting their methods, we have been using the nasal cytogram in clinical practice and find it hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Nasal cytology was firstly applied in the clinical practice at the beginning of the twentieth century, when Eyermann identified some eosinophils in the nasal mucosa of allergic patients [ 20 ], but only much later, in the 1970s in a random manner [ 21 ], and more systematically from the 2000s [ 22 ], nasal cytology found its role in nasal diagnostic algorithm. The successive wide application of nasal cytology in rhinology derives from the simplicity of normal nasal mucosa structure, which is formed by a ciliated pseudostratified epithelium, composed of mucosecreting cells and ciliated, striated, and basal cells [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nasal cytology was firstly applied in the clinical practice at the beginning of the twentieth century, when Eyermann identified some eosinophils in the nasal mucosa of allergic patients [ 20 ], but only much later, in the 1970s in a random manner [ 21 ], and more systematically from the 2000s [ 22 ], nasal cytology found its role in nasal diagnostic algorithm. The successive wide application of nasal cytology in rhinology derives from the simplicity of normal nasal mucosa structure, which is formed by a ciliated pseudostratified epithelium, composed of mucosecreting cells and ciliated, striated, and basal cells [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Nasal cytology provides an important contribution to the definition and understanding of the pathophysiological mechanisms of allergic and non-allergic rhinitis. [15][16][17] Mast cells and eosinophils are not cells specific to allergic rhinitis. In this study, we comparatively assessed cells that have a role in the pathogenesis of allergic rhinitis in nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Based on his experience with 10,000 specimens from 1000 allergic patients over a 12‐year period, Hansel reported that nasal eosinophilia was strongly associated with allergy, whereas neutrophils were associated with infection. Bryan and Bryan 54 coined the term “cytogram” to describe the mixture of epithelial and goblet cells, leukocytes, and mast cells in nasal secretions and, along with others, 55 believed that they could distinguish allergy, bacterial infection, viral infection, and vasomotor rhinitis from such an examination. No recent investigators have shown a similar expertise.…”
Section: Laboratory Tests For Diagnosing Sinonasal Disordersmentioning
confidence: 99%